JADID CAUSTIC SINGER POETRY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article examines the poems of the famous Uzbek poet Khamza, included in the collection "Folk poems on folk songs". The poet's poetry expresses the ideas of the Enlightenment, his contribution to modern poetry is emphasized. The article also analyzes the ideas of nationalism, freedom and freedom in Hamza's poems and draws certain conclusions.